Peranan Sistem Digital Accounting Terhadap Perkembangan Bisnis UMKM Di Sidoarjo - Fanniar Aurelia; Feby Galih Saputra; Gabrielle Michaela K (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
This study aims to examine the effect of digital accounting systems on business development for UMKM in Sidoarjo. This research uses a qualitative approach with a case study method. The population in this study are SMEs in Sidoarjo who use a digital accounting system, and the sample is taken using a purposive sampling technique. The data in this study were collected using in-depth interview techniques and relevant sources on the internet. Data analysis was performed using qualitative analysis. The results of the study show that the use of digital accounting systems has a significant influence on business development for UMKM in Sidoarjo. In its use, the digital accounting system simplifies the process of recording and reporting finances, as well as assisting UMKM owners in making more precise and accurate business decisions. In addition, the use of digital accounting systems also helps UMKM in increasing the efficiency and effectiveness of business operations, so as to produce better business performance. In this case, it is advisable for UMKM in Sidoarjo to adopt a digital accounting system as part of their business development strategy. This will help UMKM improve their business performance and compete with other UMKM. In addition, the government can also provide support and assistance to UMKM to adopt digital accounting systems, so as to accelerate the growth of UMKM in Indonesia.